PENGARUH EARNING PER SHARE, PRICE EARNING RATIO DAN RETURN ON ASSET TERHADAP RETURN SAHAM DENGAN KEBIJAKAN DIVIDEN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2020 – 2023 - Achmad Suyuti; Lita Permata Sari; Minullah Minullah (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the influence of Earnings Per Share, Price to Earnings Ratio, and Return on Assets on Stock Returns with Dividend Policy as an Intervening Variable in Commercial Bank Companies Listed on the Indonesia Stock Exchange in 2020-2023. The purpose of this study is to analyze the influence of Earnings Per Share (EPS), Price to Earnings Ratio (PER), and Return on Assets (ROA) on stock returns and dividend policy, as well as the mediating role of stock returns in this relationship. The analysis method used path analysis with hypothesis testing based on the path coefficient, T-statistic, and p-value. The results showed that EPS had a positive and significant effect on stock returns (coefficient = 0.572; p-value = 0.000), while PER and ROA had no significant effect. Furthermore, stock returns were shown to have a very strong effect on dividend policy (coefficient = 0.993; p-value = 0.000). Mediation analysis revealed that stock returns fully mediated the relationship between EPS and dividend policy (indirect effect = 0.568; p-value = 0.000), but did not mediate the relationship between PER and ROA and dividend policy. This finding implies that increasing EPS can drive higher stock returns, which ultimately influences a company's dividend policy. Meanwhile, PER and ROA did not have a significant impact either directly or indirectly.